Pre- and post-operative low prognostic nutritional index influences survival in older patients with gastric carcinoma. Issue 6 (July 2020) - Sugawara, Kotaro; Aikou, Susumu; Yajima, Sho; Uemura, Yukari; Okumura, Yasuhiro; Nishida, Masato; Yagi, Koichi; Yamashita, Hiroharu; Seto, Yasuyuki
Abstract: Objectives: The survival impact of the preoperative prognostic nutritional index (PNI) has been investigated in older patients with gastric carcinoma (GC), while that of the postoperative PNI has yet to be addressed. We evaluated the significance of PNI before and after surgery in older GC patients (≥75 years). Materials and Methods: In total, 309 older GC patients undergoing radical gastrectomy between 2006 and 2016 were retrospectively reviewed. The PNI was evaluated before and at six months after gastrectomy. Patients were divided into low (<45) and high (≥45) PNI groups. The impact of low PNI on overall survival (OS), cancer-specific survival (CSS), and non-GC-related death were investigated. Results: Low PNI was present in 134 patients (43.4%) preoperatively and 121 (39.2%) postoperatively. Low pre-PNI was independently associated with poor overall survival ( P  < .001). Similarly, OS was significantly stratified by post-PNI ( P  < .001). The significant survival difference according to post-PNI was present only in pStage I disease ( P  < .001). Low post-PNI independently increased the risk of non-GC-related death in a multivariable analysis ( P  = .002). In contrast, CSS was not stratified by post-PNI ( P  = .45). In the high pre-PNI group, total gastrectomy and super-older age (≥80 years) independently increased the risk of low post-PNI, which was significantly associated with poor survival outcomes. Conclusions: Pre- and post-operative PNI are useful for predicting long-term outcomes in older patients with GC. Low postoperative PNI is a powerful determinant of mortality due to other diseases. Optimal perioperative management is required for those at high risk of malnutrition postoperatively.